PENGUATAN KAPASITAS GURU SEBAGAI DA’I MELALUI WORSKSHOP PENERAPAN MANAJEMEN DA’WAH - Araniri, Nuruddin; Maulana Jamaludin, Gilang; Nahriyah, Syafa’atun (JURNAL PARAHITA ABDIMAS: Jurnal Pengabdian Masyarakat, 2020)
The capacity of elementary school teachers as Da'i is a supporter of the professional competence of teachers who must continue to be developed, especially through self-development. The capacity as a Da'i is useful for teachers in carrying out tasks in school is closely related to the obligation to develop religious spiritual competencies and as a provision in developing social competencies in the community. Facts on the field many obstacles faced by teachers in preaching, especially in the application of management as a support for success. So, capacity building through the implementation of management is the right solution to meet the needs of teachers in solving da'wah management problems. The workshop consists of two stages, namely the stage of socialization and practice. The results obtained were good, the participants gained additional knowledge and understanding of da'wah theory and were skilled in applying da'wah management so that their capacity as Da'i was stronger.